Conformism vs. Independent Opinions: The Challenges Facing Education Administration Students when Dealing with Political Conflicts Practiced in Simulation-Based Learning - Zamir , Sara; Crystal , Edna Nahon-; Abu-Jaber , Saleem (Journal of Ecohumanism, 2024)
Israel is defined as a Jewish and a democratic state. Yet, in recent years, the government of Israel has attempted to change the balance of power between the judiciary and the legislative and executive authorities. Many perceived this change as a fatal blow to democracy, while others supported the change. These political conflicts cannot be ignored inside schools. The purpose of this study was to examine how education administration M.A students deal with political conflicts within schools and the communication strategies they use. To that end, the method of simulation-based learning was used. The main research questions focused on the study participants’ willingness to express their opinions about controversial political conflicts. The results revealed an unexpected scenario. Even though school principals might be expected to be in control because of their powerful position in the organization’s hierarchy and their authority to mete out punishments and rewards, the simulations showed a different outcome in the broader political context, indicating that a general sense of chaos reigned in schools as well. Following these results, we developed a didactic educational model whose purpose is to educate toward social involvement and the ability to express a reasoned opinions.